Defining 'healthy' in preschool‐aged children for forced oscillation technique reference equations. Issue 4 (5th October 2017) - Shackleton, Claire; Czovek, Dorottya; Grimwood, Keith; Ware, Robert S.; Radics, Bence; Hantos, Zoltan; Sly, Peter D.
ABSTRACT: Background and objective: Selecting 'healthy' preschool‐aged children for reference ranges may not be straightforward. Relaxing inclusion criteria for normative data does not affect spirometry z‐scores. We therefore investigated the effect of similarly relaxing inclusion criteria in preschoolers on reference ranges for respiratory impedance (Zrs) using a modified forced oscillation technique (FOT). Methods: The International Study of Asthma and Allergies in Childhood questionnaire classified 585 children into a healthy and five mutually exclusive groups. Zrs was measured between 4 and 26 Hz and resistance (R) and compliance (C) obtained by model fitting. Prediction models were determined using mixed effect models and z‐scores compared between healthy children and the five groups. Results: Zrs data were obtained for 494 participants (4.30 ± 0.7 years) on 587 occasions. Comparison of the Zrs z‐scores between the healthy children and the health groups found significant differences in children with asthma, current wheeze and respiratory symptoms, but not in children born preterm or with early‐life wheeze. Adding these two groups to the healthy dataset had no significant effect on the distribution of z‐scores and increased the size of the dataset by 22.3%. Conclusion: Our data suggest that preschool‐aged children born preterm or with early‐life wheeze can be included in FOT reference equations, while those with asthma, current wheeze and respiratory symptoms within 4 weeks of testing should be excluded. This more inclusive approach results in more robust FOT reference ranges. Abstract : See related Editorial Normative data for respiratory impedance (Zrs) measured with the forced oscillation technique in preschool‐aged children use strict criteria to define healthy. Zrs z‐scores in preterm‐births and early‐life wheezers did not differ from healthy children allowing a more inclusive approach for reference equations, without losing discriminative power for detecting lung disease.